Risk stratification in nonischemic dilated cardiomyopathy using CMR imaging: a systematic review and meta-analysis - Eichhorn, Christian; Koeckerling, David; Reddy, Rohin K.; Ardissino, Maddalena; Rogowski, Marek; Coles, Bernadette; Hunziker, Lukas; Greulich, Simon; Shiri, Isaac; Frey, Norbert; Eckstein, Jens; Windecker, Stephan; et al. (The journal of the American Medical Association, 2024)
Accurate risk stratification of nonischemic dilated cardiomyopathy (NIDCM) remains challenging.To evaluate the association of cardiac magnetic resonance (CMR) imaging-derived measurements with clinical outcomes in NIDCM.MEDLINE, Embase, Cochrane Library, and Web of Science Core Collection databases were systematically searched for articles from January 2005 to April 2023.Prospective and retrospective nonrandomized diagnostic studies reporting on the association between CMR imaging-derived measurements and adverse clinical outcomes in NIDCM were deemed eligible.Prespecified items related to patient population, CMR imaging measurements, and clinical outcomes were extracted at the study level by 2 independent reviewers. Random-effects models were fitted using restricted maximum likelihood estimation and the method of Hartung, Knapp, Sidik, and Jonkman.All-cause mortality, cardiovascular mortality, arrhythmic events, heart failure events, and major adverse cardiac events (MACE).A total of 103 studies including 29687 patients with NIDCM were analyzed. Late gadolinium enhancement (LGE) presence and extent (per 1%) were associated with higher all-cause mortality (hazard ratio [HR], 1.81 [95% CI, 1.60-2.04]; P < .001 and HR, 1.07 [95% CI, 1.02-1.12]; P = .02, respectively), cardiovascular mortality (HR, 2.43 [95% CI, 2.13-2.78]; P < .001 and HR, 1.15 [95% CI, 1.07-1.24]; P = .01), arrhythmic events (HR, 2.69 [95% CI, 2.20-3.30]; P < .001 and HR, 1.07 [95% CI, 1.03-1.12]; P = .004) and heart failure events (HR, 1.98 [95% CI, 1.73-2.27]; P < .001 and HR, 1.06 [95% CI, 1.01-1.10]; P = .02). Left ventricular ejection fraction (LVEF) (per 1%) was not associated with all-cause mortality (HR, 0.99 [95% CI, 0.97-1.02]; P = .47), cardiovascular mortality (HR, 0.97 [95% CI, 0.94-1.00]; P = .05), or arrhythmic outcomes (HR, 0.99 [95% CI, 0.97-1.01]; P = .34). Lower risks for heart failure events (HR, 0.97 [95% CI, 0.95-0.98]; P = .002) and MACE (HR, 0.98 [95% CI, 0.96-0.99]; P < .001) were observed with higher LVEF. Higher native T1 relaxation times (per 10 ms) were associated with arrhythmic events (HR, 1.07 [95% CI, 1.01-1.14]; P = .04) and MACE (HR, 1.06 [95% CI, 1.01-1.11]; P = .03). Global longitudinal strain (GLS) (per 1%) was not associated with heart failure events (HR, 1.06 [95% CI, 0.95-1.18]; P = .15) or MACE (HR, 1.03 [95% CI, 0.94-1.14]; P = .43). Limited data precluded definitive analysis for native T1 relaxation times, GLS, and extracellular volume fraction (ECV) with respect to mortality outcomes.The presence and extent of LGE were associated with various adverse clinical outcomes, whereas LVEF was not significantly associated with mortality and arrhythmic end points in NIDCM. Risk stratification using native T1 relaxation times, extracellular volume fraction, and global longitudinal strain requires further evaluation.